Reintervention following stage 1 palliation: A report from the NPC‐QIC Registry. (10th August 2018) - Buelow, Matthew W.; Rudd, Nancy; Tanem, Jena; Simpson, Pippa; Bartz, Peter; Hill, Garick
Abstract: Background: Single ventricle heart disease with aortic arch hypoplasia has high morbidity and mortality, with the greatest risk after stage 1 palliation. Residual lesions often require catheter‐based or surgical reintervention to minimize risk. We sought to describe the types, frequency, and risk factors for re‐intervention between stage 1 and stage 2 palliation, utilizing the National Pediatric Cardiology Quality Improvement Collaborative (NPC‐QIC) registry. Methods: The NPC‐QIC registry, consisting of patients discharged after stage 1 palliation, was queried. Hybrid stage 1 palliation patients were excluded from this study. The primary risk factor was shunt type and the primary outcome was re‐intervention. Results: Of 1156 patients, (50%) had re‐intervention. There was no difference in total rate of re‐intervention by shunt type (BT shunt 52% vs. RVPA shunt 48%; P  = .17). Patients with a BT shunt had increased re‐intervention during stage 1 hospitalization ( P  =.002). During the interstage period, following discharge from stage 1 palliation, patients with a BT shunt had increased aortic arch re‐intervention ( P  < .005), while patients with an RVPA shunt had increased re‐intervention on the shunt and the pulmonary arteries ( P  = .02). Postoperative mechanical ventilation >14 d ( P  < .01) was the only risk factor associated with re‐intervention by multivariable analysis, regardless of shunt type. Conclusions: Re‐intervention between stage I and stage 2 palliation is common. There is no difference in cumulative frequency of re‐intervention between shunt types, though types and timing of re‐intervention varied between shunt types. Longitudinal assessment of the NPC‐QIC database is important to identify long term outcomes of patients requiring re‐intervention.